2020
DOI: 10.1038/s41598-020-72932-5
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolization and recovery of viable murine norovirus in an experimental setup

Abstract: Noroviruses are the major cause for viral acute gastroenteritis in the world. Despite the existing infection prevention strategies in hospitals, the disease continues to spread and causes extensive and numerous outbreaks. Hence, there is a need to investigate the possibility of airborne transmission of norovirus. In this study, we developed an experimental setup for studies on the infectivity of aerosolized murine norovirus (MNV), a model for the human norovirus. Two aerosol generation principles were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In La Paz, we detected norovirus GII at the highest average density across all targets (13 gc/m air 3 ) and norovirus GI at a mean of 2.4 gc/m air 3 . Norovirus is relatively resistant to inactivation in environmental media, may persist on environmental surfaces for up to 2 weeks, has been shown to survive in aerosols, and has an estimated relatively low median infectious dose between 18 and 10 3 virus particles . It is among the most widely prevalent viral enteric pathogens, globally, with estimated 33 000 cases and 20 000 deaths per year. ,, Norovirus transport through bioaerosols and subsequent deposition and indirect exposure through ingestion remain poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…In La Paz, we detected norovirus GII at the highest average density across all targets (13 gc/m air 3 ) and norovirus GI at a mean of 2.4 gc/m air 3 . Norovirus is relatively resistant to inactivation in environmental media, may persist on environmental surfaces for up to 2 weeks, has been shown to survive in aerosols, and has an estimated relatively low median infectious dose between 18 and 10 3 virus particles . It is among the most widely prevalent viral enteric pathogens, globally, with estimated 33 000 cases and 20 000 deaths per year. ,, Norovirus transport through bioaerosols and subsequent deposition and indirect exposure through ingestion remain poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses may be highly mobile in aerosols, but would not be captured in 16S rRNA sequencing that represents the bulk of analytical methods used in bioaerosols analysis. The available evidence from our review and other emerging evidence 44 suggests that enteric viruses are important potential targets in urban aerosols, particularly norovirus given its well documented transport in aerosols [141][142][143][144] . Of the studies that employed methods that would be suited to the detection of enteric viruses (6 out of 101 covered in this review), 33% (n=2) identified them, including detections of human enterovirus, human rotavirus, and human adenovirus (Table 2).…”
Section: Discussionmentioning
confidence: 83%
“…In La Paz, we detected norovirus GII at the highest average density across all targets (13 gc/m 3 air ) and norovirus GI at a mean of 2.4 gc/m 3 air . Norovirus is relatively resistant to inactivation in environmental media 120 , may persist on environmental surfaces for up to two weeks 121 , has been shown to survive in aerosols [122][123][124][125][126] , and has an estimated relatively low median infectious dose between 18 and 10 3 virus particles 127 . It is among the most widely prevalent viral enteric pathogens, globally, with an estimated 33,000 cases and 20,000 deaths per year 115,128,129 .…”
Section: Discussionmentioning
confidence: 99%